VIRTUAL REALITY TOOLS FOR PAIN MANAGEMENT (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2021)
Pain control is a difficult task to accomplish, especially without using potentially addictive drugs like opioids. Failure in providing a comprehensive pain control plan by using opioids can lead to lowering the quality of life and addiction that will further worsen the patient's condition. In the last years, immersion in Virtual Reality proved its value as a technique for clinical pain management to accompany and lower the regular opioid dosage. The current paper describes this technique, as well as the novelties introduced by our team in a gamified VR setting for pain management.
Keywords: Virtual reality; Pain management; Acute pain; Attention